1996
DOI: 10.1159/000227637
|View full text |Cite
|
Sign up to set email alerts
|

The Severity and Pattern of Emesis following Different Cytotoxic Agents

Abstract: Different cytotoxic drugs induce different patterns of emesis. This is relevant to clinical practice since we often see in the medical literature oversimplifications in the recommendation for management of chemotherapy-induced emesis, so that the same guidelines are given for cisplatin and non-cisplatin-containing chemotherapy. In particular, cisplatin induces a biphasic pattern of emesis which is characterized by an acute immediate phase and a delayed phase. These two phases are clearly different, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 9 publications
2
72
0
Order By: Relevance
“…The current review has demonstrated that the clinical objective of preventing emesis will be achieved only when the 5-HT 3 ) concur that these agents should be given in combination with a corticosteroid to patients who are at high or moderate risk of developing emesis. These guidelines also provide a dosing guide for the use of 5-HT 3 receptor antagonists, although they are at variance with each other and with the recommendations laid out by the manufacturers.…”
Section: Discussionmentioning
confidence: 93%
“…The current review has demonstrated that the clinical objective of preventing emesis will be achieved only when the 5-HT 3 ) concur that these agents should be given in combination with a corticosteroid to patients who are at high or moderate risk of developing emesis. These guidelines also provide a dosing guide for the use of 5-HT 3 receptor antagonists, although they are at variance with each other and with the recommendations laid out by the manufacturers.…”
Section: Discussionmentioning
confidence: 93%
“…This greater benefit with aprepitant may be due to the higher level of emetogenicity produced by combinations of chemotherapeutic agents, as well as by the mechanisms of emetogenicity of the concomitant agents themselves. Cyclophosphamide-induced vomiting, which occurs in a monophasic rather than biphasic pattern and produces a different profile of plasma serotonin levels and urinary excretion of 5-hydroxyindole acetic acid compared with cisplatin, 24,25 may be centrally mediated, possibly involving NK 1 receptors at which aprepitant exerts its antagonistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed emesis starts at least 24 h after cancer therapy and may last for more than 5 days, with a peak incidence at around day 2–3 depending upon the agent [89,90,91,92] (fig. 3).…”
Section: -Ht3-receptor Antagonists In Delayed Emesismentioning
confidence: 99%